Rebuttal: "Comments on 'Energy intensities, EROIs (energy returned on invested), and energy payback times of electricity generating power plants' – Making clear of quite some confusion". (15th March 2015) - Raugei, Marco; Carbajales-Dale, Michael; Barnhart, Charles J.; Fthenakis, Vasilis
Highlights: Serious methodological errors in a paper by Weißbach et al. invalidate their results. The origin of such errors is investigated and explained. Weißbach et al.'s findings and conclusions are rebutted.